Fracture resistance of monolithic translucent zirconia crown bonded with different self-adhesive resin cement: influence of MDP-containing zirconia primer after aging - Shaima Tyor; Walid Al-Zordk; Amal Abdelsamad Sakrana (BMC, 2023)
Abstract Objectives Successful ceramic restorations depend on the strong bonding with resin cement and even stress distribution. The aim of this study was to evaluate the impact of adding MDP-containing zirconia primer before self-adhesive resin cements with different functional acidic monomers on fracture resistance of monolithic zirconia crown. Materials and methods Eighty defect-free human maxillary premolars were divided according to the cement type and application of MDP-containing zirconia primer into eight groups (n = 10): Calibra Universal (C), Calibra Universal combined with zirconia primer (CZ), RelyX U200 (R), RelyXU200 combined with zirconia primer (RZ), Panavia SA Cement Plus (P), Panavia SA Cement Plus combined with zirconia primer (PZ), Multilink Speed (M), and Multilink Speed combined with zirconia primer (MZ). After teeth preparation and fabrication of zirconia crowns, each crown was bonded to its corresponding tooth. All specimens were subjected to 10,000 thermocycles between 5 and 55°C, followed by cyclic load (50 N) for 240,000 cycles. Each specimen was subjected to a static axial load until fracture using universal testing machine and the fracture load was recorded. The fracture mode studied and recorded. The fracture load results were analyzed using two-way ANOVA test (α = 0.05). Results A significant interaction (P = 0.038) of combining MDP-containing zirconia primer and cement type on fracture resistance of monolithic zirconia crown was detected. The mean fracture load values of zirconia crown were significantly influenced by the combined application of the MDP-containing zirconia primer with Calibra Universal (P = 0.01), RelyX U200 (P < 0.001), and Multilink Speed (P = 0.038), while there was no significant difference with Panavia SA Cement Plus (P = 0.660). There was significant difference (F = 20.69, P < 0.001) between the mean fracture loads of groups with self-adhesive cements (C, R, P, and M groups). The highest fracture load was recorded with RZ group (2446.90 ± 126.72 N) while the lowest fracture load was recorded with C group (1623.18 ± 149.86 N). Conclusions The self-adhesive resin cement with different acidic functional monomer affects the fracture resistance of monolithic zirconia crown. Application of MDP-containing primer could improve the fracture resistance of monolithic zirconia crown with most self-adhesive cements. The application of an MDP-containing primer had no impact on the fracture resistance of monolithic translucent zirconia crown bonded by MDP-containing self-adhesive resin cement.